E-PORTFOLIO AS AN AUTHENTIC LEARNING ASSESSMENT IN A RESPONSE TO COVID-19 OUTBREAK IN INDONESIAN HIGHER EDUCATION: TOWARD CRITICAL STUDENT-WRITERS - Misdi, Misdi (Research And Innovation In Language Learning (RILL), 2020)
This report, a part of a larger study, describes a case study investigating university educators who struggled in empowering student-teachers that aimed to promote critical writing awareness. This study aimed at revealing phenomenon of edmodo-based e-portfolio as an alternative authentic assessment for empowering student teachers in the covid-19 outbreak in Indonesia. Twenty-five out of seventy-eight student teachers in teacher college in Indonesia voluntarily participated in the study. For the data, the student teachers were observed during their writing completion to assess their writing as well as their critical arguments. At the end of the first writing project, they were interviewed to reveal their attitudes towards the projects.  Three main findings were reported, i.e. their writing skill improvement, attitudes, and critical writing. Overall, the findings show that edmodo-based portfolio provides graphic of students? writing performance as authentic writing assessment and perceives positive attitudes from the student teachers. In addition, students? critical writing awareness is also developed